POTENSITRICHODERMA SP. DANGLIOCLADIUM SP. SEBAGAI MIKROBA ANTAGONIS TERHADAPFUSARIUM OXYSPORUM F.SP.CUBENSE - SUDARMA, I MADE (Agrotrop : Journal on Agriculture Science, 2012)
Potency of Trichoderma sp. and Gliocladium sp. as microbial antagonist on Fusarium oxysporum f.sp. cubense A total of 115 different fungus isolate were recovered from banana crop habitats with and without Fusarium wilt disease symptom. These were than assessed for their antagonist ability againstFusarium oxysporum f.sp.cubense (Foc)in vitro.The soil samples were collected from three regencies in Bali, i.e. Karangasem, Klungkung and Jembrana which are the main banana growing areas in Bali. Soil sampling was done in two sites in each regency representing the banana habitat with and without Fusarium wilt symptom, by collecting 100 grams of soil surrounding the banana plant at the depth of 20 cm. The isolate was macroscopically identified to know the color of colony and the growth rate, and microscopically to observe the shape of hypae, the shape of spore, and sporangiospore. The research was done on August until December 2009. Results indicated that one isolates ofGliocladium sp. and 22 isolates of Trichoderma sp. active against Foc. Trichoderma sp. was able to inhibit the Foc mycelium growth were 78.89 ± 1.11- 95.83 ± 7.22 % and Gliocladium sp. inhibited until 95.83 ± 7.22%. After tested with the Foc isolated from four banana cultivars in Bali (Saba, Ketip, Susu and Raja), all of the isolates was able to inhibit the Focin vitro.
Keywords: microbial antagonist,Fusarium oxysporum f.sp.cubense, and inhibited ability